Explicating Environmental Patriarchy: An Examination Through Gender and Environment Perspectives. Issue 2 (December 2019) - Dalal, Anjali
Much has been written about the relationship between women, nature and development, a relationship where women's work, like nature, is often undervalued, in terms of acknowledging the interdependence of women and nature in preservation of environment to foster sustainable growth. Women are perceived as prominent actors in domestic chores as well as contributors to environmental rehabilitation and conservation. However, in comparison to men, their work and knowledge have often been undervalued in both environmental planning and domestic resource management. The existence of environmental patriarchy is, thereby, located at three dimensions; first, women's exclusion from resource ownership and management; second, women's exclusion from deliberation of indigenous knowledge; and third, gendered power relationship in society. This article explores the region-specific concerns of women built into theoretical feminist perspectives of the Western world in contrast to the Third World countries, dealt within a theoretical perspective of ecofeminism and feminist environmentalism. However, both the models leave some major theoretical questions unanswered, finally concluded in a perspective as proposed by feminist political ecology. The idea behind doing this is to take account of the various ways of conceptualizing feminist ecological theories so as to emphasize greater role of women in environmental planning and decision-making processes. By simultaneously analysing some environmental movements, it was found that women's activism was not only sustainable but confronted other social issues and patriarchy in private domain.